Exploring Technology Acceptance Aspects of an NFC Enabled Mobile Shopping System: Perceptions of German Grocery Consumers - Bast, Erik (Auckland University of Technology, 2011)
It is envisaged that with the increasing radio frequency identification (RFID) penetration along the grocery supply chain, a Near Field Communication (NFC) mobile shopping assistant is highly likely to be developed. Such a device would provide the customer with product specific information at the point of shopping. In order to investigate different aspects of this possibility, several potential users were interviewed after they had some familiarisation with a prototype smartphone-based application. Benefits, issues and challenges were identified. The benefits were: customers can read information of products they are already familiar with; certain information types were easier to read compared to traditional labels; and, additional information supported product selection. The issues were: security vulnerabilities because the technologies (smartphone, RFID, background systems and databases) exposed the customer to threats to their personal data; the increased public use of expensive smartphones could attract thieves; and, the short life of a smartphone battery and interference of phonecalls. The challenges were: balancing desired variety and amount of grocery product information in contrast to easy to use software; and, balancing the costs for the service, device, information and support without charging the customer too high usage fees. Personalized advertisements were suggested to subsidise the cost but the customer behaviour profiling would be an additional threat to privacy. Development of some types of NFC mobile shopping assistant would seem inevitable. This research has revealed that developers and owners of such a technology will need to be alert to the issues and challenges identified in this research. Future research of user behaviour and preferences across different cultures, age groups and user types would assist further progress.
Keywords: NFC; RFID; TAM; Mobile; Grocery; Germany; Supply chain; Costs; Privacy; Security; Usefulness; Ease of use; Smartphone; Mobile shopping assistant